Friendship With God?: Variations on a Theme in Aristotle, Aquinas, and Macmurray - Zemler-Cizewski, Wanda (Philosophy & theology, 1992)
First I investigate the concept of friendship in Aristotle’s Nicomachean Ethics, books eight and nine. Next, I touch on some of the distinctively Christian aspects of the concept of friendship in Thomas Aquinas’s though, with particular attention to the virtue of caritas as friendship with God. Having by these means gained some perspective on the problem, I describe the new direction taken by Macmurray’s interpretation of friendship, and especially the question of friendship with God.